Native Students and the Special Mature Students Program at the University of Manitoba: An Historical Examination - Matthiasson, John S.; Kristjanson, Ronald W. (Culture, 1981)
With an increasing public concern in the past decade over the socio-economic position of the native peoples of Canada, in large part a response to the politicization of native peoples themselves, special educational programmes have been initiated at several Canadian universities. The majority of students in the Special Mature Students Program of the University of Manitoba are of native background. This article examines some of the difficulties encountered during the first years of that program, ways in which they have been resolved, and factors related to the success of those students of native background who have completed first degrees and/or been admitted to professional faculties.